Recovery of Valuable Solutes from Organic Solvent/Water Mixtures via Direct Contact Membrane Distillation (DCMD) as a Non-Heated Process - Yuki Suga; Ryosuke Takagi; Hideto Matsuyama (Membranes, 2021)
Recently, the demand for the recovery of valuable solutes from organic solvents/water mixtures has increased in various fields. Furthermore, due to the abundance of heat-sensitive valuable solutes, the demand for non-heated concentration technologies has increased. In this study, the direct contact membrane distillation (DCMD) using hydrophobic polyvinylidene difluoride (PVDF) hollow fiber membranes was investigated to confirm the possibility of recovering valuable solutes from organic solvents/water mixtures as a non-heated process. The DCMD with 1000 ppm NaCl aqueous solution achieved 0.8 kg/m2·h of vapor flux and >99.9% of NaCl retention, even at feed and coolant temperatures of 25 and 10 °C, respectively. Furthermore, when DCMD was conducted under various conditions, including feed temperatures of 25, 35 and 45 °C, and organic solvent concentration of 15, 30 and 50 wt%, using ethanol/water and acetonitrile/water mixtures containing 1000 ppm NaCl. A surfactant was also used as a valuable solute, in addition to NaCl. As a result, it was found that the total vapor flux increased with increasing temperature and concentration of organic solvents, as the partial vapor pressure of the organic solvents increased. Additionally, no solute leaked under any condition, even when the surfactant was used as a valuable solute.